2015
DOI: 10.1177/1077699015596337
|View full text |Cite
|
Sign up to set email alerts
|

Making Change

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link Abstract:Diffusion of innovations theory typically has been applied to the spread of a particular technology or practice rather than the interplay of a cluster of innovations. This case study of a news company undergoing significant change seeks to offer a deeper understanding of multifaceted industry upheaval by considering the diffusion of three interdependent yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(38 citation statements)
references
References 38 publications
(70 reference statements)
4
28
0
Order By: Relevance
“…Results on the engagement with the audience illustrate only small aspects of relational change (RQ 2.1 and 2.2). These findings are similar to the findings by Ekdale et al (2015), who found that technological change is faster than relational or cultural change in a newsroom. Just 8% of WhatsApp messages sent by outlets contain a dimension of audience engagement (RQ 2.1).…”
Section: Conclusion and Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Results on the engagement with the audience illustrate only small aspects of relational change (RQ 2.1 and 2.2). These findings are similar to the findings by Ekdale et al (2015), who found that technological change is faster than relational or cultural change in a newsroom. Just 8% of WhatsApp messages sent by outlets contain a dimension of audience engagement (RQ 2.1).…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…The findings indicate different levels of innovation diffusion in the newsrooms analyzed with yet only few accepting the relational change coming with the technological change. This could originate in path dependencies: journalists select and edit content for WhatsApp in a similar way as for other social media before and do not change their routines, which has been observed by Lasorsa, Lewis, and Holton (2012), Ekdale et al (2015), and Broersma and Graham (2013). However, for their audience WhatsApp is a mobile, interpersonal communication app, which is used differently than other social media.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations